(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present study was undertaken to analyze the effect of turbulence training [TTGKP], combination of weight – plyometric training and combined turbulence training and Weight - Plyometric training [CTWPTGKP] on explosive power of kabaddi players. total N=60 male intercollegiate level participated men kabaddi players age ranging from 18-25 years selected from various colleges from Vizianagaram district of Andhra Pradesh . The kabaddi players chosen for the study were randomly divided into four groups each group n=15 kabaddi players i.e. one empirical group Turbulence training group kabaddi players [TTGKP], second empirical group combined weight - plyometric training group kabaddi players [CWPTGKP], three empirical group combined turbulence training and weight - plyometric training group kabaddi players [CTWPTGKP] and one control kabaddi players group [CKPG]. CKPG were restricted to participate in any activities. The trainings were given for a period of twelve weeks. The data were collected before and after the training by conducting standing broad jump. The obtained data’s were analyzed by Analysis of Covariance (ANCOVA). The level of significant was fixed at 0.05 levels. The results of the study showed that turbulence training treatment [Package I], combined weight - plyometric training treatment [Package II] and combined turbulence training and weight - plyometric training [Package III] significantly improved explosive power of the kabaddi players when comparative with control group.